Preparation method of high-strength and high-temperature nickel-manganese-gallium shape memory alloy

CN118308615BActive Publication Date: 2026-10-30HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410427769.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-10
Publication Date
2026-10-30
Estimated Expiration
2044-04-10

AI Technical Summary

Technical Problem

[0005]本发明的目的是为了解决现有的Ni-Mn-Ga形状记忆合金在超高温环境下,易发生脆性断裂,导致材料疲劳寿命低的问题,进而提供一种高强度及高温的镍锰镓形状记忆合金的制备方法

Benefits of technology

[0035]1、本发明采用了定向凝固技术将合金调整至一种少晶的状态,极大地减少合金中的晶界含量,尤其是垂直于应力方向的横向晶界,减少裂纹萌生,提高合金的力学性能、延长材料的疲劳寿命。并且通过这种方法可以制备出具有趋于定向凝固方向的初始织构的晶体组织,马氏体变体取向趋于一致,温度诱导马氏体相变可产生大的形状变化,有利于提高合金的形状记忆效应。相比于单晶制备成本低,定向凝固操作更加容易,可以更好地推进Ni-Mn-Ga合金在工程中的实际应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118308615B_ABST
    Figure CN118308615B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a high-strength and high-temperature nickel-manganese-gallium shape memory alloy, and relates to the technical field of high-temperature alloy preparation.The application solves the problem that the existing Ni-Mn-Ga shape memory alloy is prone to brittle fracture under an ultrahigh-temperature environment, and the fatigue life of the material is low.The alloy is adjusted to a few-crystal state by adopting the Bridgman method directional solidification after pretreatment, weighing, degassing and arc melting, and coarse columnar crystals parallel to the directional solidification direction are obtained, so that the grain boundary content in the alloy is greatly reduced.The existence of the gamma phase can significantly change the phase transition temperature and mechanical properties of the alloy, the martensite phase transition temperature of the alloy is greater than 400 DEG C, the compression strength is more than 1700MPa, the fracture strain is more than 17%, the shape memory recovery amount is more than 3.5%, and the initial texture of the [001] orientation is obtained.The application is used for the preparation of the nickel-manganese-gallium shape memory alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy preparation technology, specifically to a method for preparing a high-strength and high-temperature nickel-manganese-gallium shape memory alloy. Background Technology

[0002] Ni-Mn-Ga shape memory alloy is a novel functional material that utilizes martensitic phase transformation to achieve shape memory. Taking advantage of the alloy's property of exhibiting martensite at low temperatures and austenite at high temperatures, theoretically, the deformation will be completely recovered after applying external force and increasing the temperature. Ni-Mn-Ga alloy has broad application prospects in the field of intelligent drive sensing and is expected to become a smart material for the next generation of aircraft's dominant airborne actuation systems. However, currently, the phase transformation temperatures of most widely studied shape memory alloys are concentrated near room temperature, with the highest being only 120-150°C. For example, a directionally solidified NiMnFeGa magnetostrictive shape memory alloy was prepared using an ultra-high temperature gradient directional solidification device. Along the crystal growth direction, the solidification structure gradually transitions from equiaxed crystals to columnar crystals, with a significant orientation of the martensite variants, and the phases becoming increasingly fine and uniformly distributed. During heating and cooling, the alloy undergoes thermally induced martensitic and reverse phase transformations, with the martensitic phase transformation temperature reaching 147°C. However, this phase transition temperature is far from sufficient for high-temperature sensors with operating temperatures above 400℃, so there is an urgent need to develop a shape memory alloy with a high phase transition temperature.

[0003] One factor affecting the application of Ni-Mn-Ga shape memory alloys is their mechanical properties, especially their intrinsic brittleness. Because Ni-Mn-Ga alloys are intermetallic compounds, and the atomic sizes and electronic structures of Ni, Mn, and Ga atoms differ significantly, while the atoms are bonded together by metallic bonds, intergranular fracture is likely to occur, leading to brittle fracture. In polycrystalline alloys, repeated deformation and shape recovery can easily cause cracks to initiate at grain boundaries, resulting in stress concentration and reducing the material's fatigue life.

[0004] In summary, existing Ni-Mn-Ga shape memory alloys are prone to brittle fracture under ultra-high temperature conditions, resulting in low material fatigue life. Summary of the Invention

[0005] The purpose of this invention is to solve the problem that existing Ni-Mn-Ga shape memory alloys are prone to brittle fracture under ultra-high temperature conditions, resulting in low material fatigue life, and to provide a method for preparing high-strength and high-temperature nickel-manganese-gallium shape memory alloys.

[0006] The technical solution of this invention is:

[0007] A method for preparing a high-strength and high-temperature nickel-manganese-gallium shape memory alloy, wherein the nickel-manganese-gallium shape memory alloy is prepared from Ni in a molar ratio of 56%–58%, Mn in a molar ratio of 24%–26%, and Ga in a molar ratio of 17%–19%, and the method includes the following steps:

[0008] Step 1: Pre-treatment of alloying elements:

[0009] Step 2, Weighing:

[0010] Weigh the Ni particles with a diameter of 3 mm and a length of 3 mm, the electrolytic Mn flakes and the Ga block. To compensate for the evaporation loss of Mn during smelting and directional solidification, add an extra 2 wt.% of electrolytic manganese flakes during the alloy preparation process.

[0011] Step 3: Degassing:

[0012] Before melting the alloy, 100-120g of sponge titanium is melted in a water-cooled copper crucible for 2-3 minutes to remove oxides and residual oxygen in the electric arc furnace.

[0013] Step 4: Electric Arc Furnace Melting

[0014] Step 41: Place the prepared alloy components into a vacuum arc melting furnace, and evacuate the furnace to 10°C. -3 The gas is on the order of Pa and filled with high-purity argon.

[0015] Step 42: Start melting the alloy. To minimize the volatilization of Mn, control the current to no more than 250A during melting. Use electric arc stirring to homogenize the alloy. Repeat melting 4 to 5 times to finally obtain the alloy button ingot.

[0016] Step 5, Wire EDM:

[0017] The button ingots obtained in step four were cut into round bars with a diameter of 7mm by wire cutting to prepare for subsequent directional solidification melting.

[0018] Step Six: Directional Setting:

[0019] The round bar obtained in step five was placed inside a high-purity corundum ceramic tube with a diameter of 7 mm and a length of 15 mm using the Brijeman method, and the alloy was melted by electromagnetic induction heating. Finally, the sample was quickly placed into Ga-In liquid for cooling. Thus, the preparation of a high-strength and high-temperature nickel-manganese-gallium shape memory alloy was completed.

[0020] Furthermore, the pretreatment of each alloying element in step one includes the following steps:

[0021] Step 11: Select Ni granules (purity > 99.99%), electrolytic Mn flakes (purity > 99.8%), and Ga blocks (purity > 99.9%) as raw materials;

[0022] Steps 1 and 2: Before smelting, soak the Ni particles and electrolytic Mn sheets in anhydrous ethanol solution for 15 minutes, rinse and then blow dry;

[0023] Step 13: Place the Ga block in a beaker, and then place the Ga block in hot water at 90°C and wait for it to melt;

[0024] Preferably, in step one, the purity of Ni particles is >99.99%, the purity of electrolytic Mn flakes is >99.8%, and the purity of Ga blocks is >99.9%.

[0025] Furthermore, the methods for weighing Ni particles, electrolytic Mn sheets, and Ga in step two are as follows:

[0026] Step 21: Calculate the mass ratio based on the atomic ratio and the atomic mass of the elements, and weigh the Ni particles, electrolytic Mn sheets and Ga blocks using an electronic balance with an accuracy of 0.0001g.

[0027] Step 22: Use a disposable dropper to draw the molten Ga from the beaker and weigh it to obtain the required weight;

[0028] Preferably, the alloying element composition weighed in step two is Ni. 57 Mn 25 Ga 18 .

[0029] Furthermore, the method for placing the prepared alloy components into the vacuum arc melting furnace in step four-one is as follows:

[0030] Place half of the Ni particles at the bottom of the water-cooled copper crucible, then add electrolytic Mn sheets, then Ga blocks, and finally add the remaining half of the Ni particles on top.

[0031] Furthermore, in step four-two, the current is controlled at 250A during melting, and electric arc stirring is performed to homogenize the alloy, and the melting is repeated four times.

[0032] Preferably, in step six, during the process of melting the alloy using electromagnetic induction heating, the power is increased by 2KW every 5 minutes until it reaches 20KW, and then the temperature is maintained for 1 hour. After holding at this temperature, directional solidification is carried out.

[0033] Preferably, in step six, the pulling speed during the alloy melting process is 10 μm / s.

[0034] Compared with the prior art, the present invention has the following advantages:

[0035] 1. This invention employs directional solidification technology to adjust the alloy to a oligocrystalline state, significantly reducing the grain boundary content, especially the transverse grain boundaries perpendicular to the stress direction. This reduces crack initiation, improves the alloy's mechanical properties, and extends the material's fatigue life. Furthermore, this method can produce crystal structures with an initial texture tending towards the directional solidification direction. The martensite variants exhibit more uniform orientation, and temperature-induced martensitic transformation can produce significant shape changes, which is beneficial for enhancing the alloy's shape memory effect. Compared to single-crystal preparation, directional solidification is less costly and easier to perform, thus better promoting the practical application of Ni-Mn-Ga alloys in engineering.

[0036] 2. The alloy prepared by this invention has a two-phase structure of unmodulated martensite plus γ phase at room temperature. Its structure consists of coarse columnar crystals, reducing the number of grain boundaries. The presence of the γ phase significantly increases the phase transformation temperature of the alloy, with a martensitic phase transformation temperature greater than 400℃. Furthermore, it inhibits crack propagation and improves the mechanical properties of the alloy, with a compressive strength exceeding 1700 MPa and a fracture strain exceeding 17%. Combined with directional solidification technology, the final alloy exhibits a shape memory recovery of over 3.5%, achieving an initial martensitic texture with a

[001] orientation. While maintaining its excellent shape memory functionality, this significantly expands the alloy's operating temperature range and improves the material's fatigue life. Attached Figure Description

[0037] Figure 1 This is a microstructure of the high-temperature Ni-Mn-Ga alloy prepared by directional solidification in Example 1.

[0038] Figure 2 This is the XRD pattern of the high-temperature Ni-Mn-Ga alloy prepared by directional solidification in Example 1.

[0039] Figure 3 This is a DSC image of the high-temperature Ni-Mn-Ga alloy prepared by directional solidification in Example 1.

[0040] Figure 4 The figure shows the stress-strain curves of the high-temperature Ni-Mn-Ga alloy prepared by directional solidification in Example 1 under compression conditions, where (a) is the compression to a pre-strain of 10%; and (b) is the compression to fracture.

[0041] Figure 5 This is the orientation inverse pole figure of the high-temperature Ni-Mn-Ga alloy prepared by directional solidification in Example 1.

[0042] in, Figures 1 to 5The parameters in the table are: Intensity, Theta (θ), Heat flow, Temperature, Cooling, Heating, and Compression. Detailed Implementation

[0043] Specific Implementation Method 1: This implementation method discloses a high-strength and high-temperature nickel-manganese-gallium shape memory alloy, wherein the nickel-manganese-gallium shape memory alloy is prepared from Ni with a molar ratio of 56%–58%, Mn with 24%–26%, and Ga with 17%–19%, and includes the following steps:

[0044] Step 1: Pre-treatment of alloying elements:

[0045] Step 2, Weighing:

[0046] Weigh the Ni particles with a diameter of 3 mm and a length of 3 mm, the electrolytic Mn flakes and the Ga block. To compensate for the evaporation loss of Mn during smelting and directional solidification, add an extra 2 wt.% of electrolytic manganese flakes during the alloy preparation process.

[0047] Step 3: Degassing:

[0048] Before melting the alloy, 100-120g of sponge titanium is melted in a water-cooled copper crucible for 2-3 minutes to remove oxides and residual oxygen in the electric arc furnace.

[0049] Step 4: Electric Arc Furnace Melting

[0050] Step 41: Place the prepared alloy components into a vacuum arc melting furnace, and evacuate the furnace to 10°C. -3 The gas is on the order of Pa and filled with high-purity argon.

[0051] Step 42: Start melting the alloy. To minimize the volatilization of Mn, control the current to no more than 250A during melting. Use electric arc stirring to homogenize the alloy. Repeat melting 4 to 5 times to finally obtain the alloy button ingot.

[0052] Step 5, Wire EDM:

[0053] The button ingots obtained in step four were cut into round bars with a diameter of 7mm by wire cutting to prepare for subsequent directional solidification melting.

[0054] Step Six: Directional Setting:

[0055] The round bar obtained in step five was placed inside a high-purity corundum ceramic tube with a diameter of 7 mm and a length of 15 mm using the Brijeman method, and the alloy was melted by electromagnetic induction heating. Finally, the sample was quickly placed into Ga-In liquid for cooling. Thus, the preparation of a high-strength and high-temperature nickel-manganese-gallium shape memory alloy was completed.

[0056] Specific Implementation Method Two: The pretreatment of each alloying element in step one of this implementation method includes the following steps:

[0057] Step 11: Select Ni granules (purity > 99.99%), electrolytic Mn flakes (purity > 99.8%), and Ga blocks (purity > 99.9%) as raw materials;

[0058] Steps 1 and 2: Before smelting, soak the Ni particles and electrolytic Mn sheets in anhydrous ethanol solution for 15 minutes, rinse and then blow dry;

[0059] Step 13: Place the Ga block in a beaker, then place the Ga block in a 90°C water bath and wait for it to melt.

[0060] Because the Ga block is large, it is difficult to obtain the required mass of Ga in the desired proportion. However, Ga has a very low melting point of only 29.76°C. This arrangement allows the Ga block to become completely liquid, making it convenient to weigh it using a dropper later. Other components and connections are the same as in Specific Implementation Method 1.

[0061] Specific Implementation Method 3: In step one of this implementation method, the purity of Ni particles is >99.99%, the purity of electrolytic Mn sheets is >99.8%, and the purity of Ga blocks is >99.9%.

[0062] This configuration reduces impurities and oxides in the alloy, preventing them from affecting the alloy's mechanical properties and shape memory effect. Other compositional and connectivity relationships are the same as in specific implementation methods one or two.

[0063] Specific Implementation Method Four: The method for weighing Ni particles, electrolytic Mn sheets, and Ga in step two of this implementation method is as follows:

[0064] Step 21: Calculate the mass ratio based on the atomic ratio and the atomic mass of the elements, and weigh the Ni particles, electrolytic Mn sheets and Ga blocks using an electronic balance with an accuracy of 0.0001g.

[0065] Step 22: Use a disposable dropper to draw the molten Ga from the beaker and weigh it to obtain the required weight.

[0066] This configuration avoids introducing other impurities during the weighing process. Other components and connections are the same as in specific implementation methods one, two, or three.

[0067] Specific Implementation Method Five: The alloying element composition weighed in step two of this implementation method is Ni. 57 Mn 25 Ga 18 This configuration ensures that the alloy's microstructure contains both martensite and γ-phase, resulting in good ductility and toughness. Furthermore, since martensite is the dominant component, it also possesses the alloy's functional properties. Other compositions and bonding relationships are the same as in any of the specific embodiments one through four.

[0068] Specific Implementation Method Six: The method for placing the prepared alloy components into the vacuum arc melting furnace in step four-one of this implementation method is as follows:

[0069] Place half of the Ni particles at the bottom of the water-cooled copper crucible, then add electrolytic Mn sheets, then Ga blocks, and finally add the remaining half of the Ni particles on top.

[0070] This configuration aims to reduce losses caused by component volatilization or sputtering during the smelting process, which could lead to uneven and inaccurate alloy composition. Other components and connections remain the same as in any of the specific embodiments one through five.

[0071] Specific implementation method seven: In step four two of this implementation method, the current is controlled at 250A during melting, and electric arc stirring is performed to homogenize the alloy. The melting is repeated 4 times.

[0072] This configuration minimizes the volatilization of Mn, ensuring the uniformity and accuracy of the alloy composition. Other components and connections remain the same as in any of the specific embodiments one through six.

[0073] Specific Implementation Method Eight: In step six of this implementation method, during the alloy melting process using electromagnetic induction heating, the power is increased by 2KW every 5 minutes until it reaches 20KW, then held at a constant temperature for 1 hour, followed by directional solidification. This setup ensures complete melting of the alloy and maintains the homogeneity of the melt composition. Other components and connection relationships are the same as in any one of Specific Implementation Methods One to Seven.

[0074] Specific Implementation Method Nine: In step six of this implementation method, the pulling speed during the alloy melting process is 10 μm / s. This setting allows for the introduction of coarse columnar crystals into the alloy. Other composition and connection relationships are the same as in any one of Specific Implementation Methods One to Eight.

[0075] In summary, this invention discloses a method for preparing a high-strength and high-temperature nickel-manganese-gallium shape memory alloy. The alloy is prepared from Ni with a molar ratio of 56%–58%, Mn of 24%–26%, and Ga of 17%–19%. After pretreatment, weighing, degassing, and arc melting, the alloy is finally adjusted to a oligocrystalline state using Bridgeman directional solidification, resulting in coarse columnar crystals parallel to the directional solidification direction, significantly reducing the grain boundary content. The presence of the γ phase significantly improves the alloy's phase transformation temperature and mechanical properties. The alloy exhibits a martensitic phase transformation temperature greater than 400℃, compressive strength exceeding 1700 MPa, fracture strain exceeding 17%, shape memory recovery exceeding 3.5%, and an initial texture with

[001] orientation. While maintaining the alloy's excellent shape memory functionality, the working temperature range is greatly improved, enhancing the material's fatigue life. These advantages can better promote the practical application of Ni-Mn-Ga shape memory alloys in engineering.

[0076] The following will combine Figures 1 to 5 The embodiments of the present invention will be described in detail below.

[0077] Example 1:

[0078] The Ni-Mn-Ga shape memory alloy prepared by directional solidification in this embodiment is prepared by a molar ratio of 57% Ni, 25% Mn and 18% Ga.

[0079] This embodiment describes a method for preparing Ni-Mn-Ga shape memory alloys using directional solidification, comprising the following steps:

[0080] Step 1: Pretreatment: Select Ni granules (purity > 99.99%), electrolytic Mn flakes (purity > 99.8%), and Ga blocks (purity > 99.9%) as raw materials. Before melting, soak the Ni granules and electrolytic Mn flakes in anhydrous ethanol solution for 15 minutes, rinse, and then dry. Place the Ga blocks in a beaker and then immerse them in 90°C hot water until melting.

[0081] Step 2, Weighing: Calculate the mass ratio based on the atomic ratio and the atomic mass of the elements, and weigh each component using an electronic balance with an accuracy of 0.0001g. The molten Ga is drawn from the container using a disposable dropper and weighed to obtain the required weight. To compensate for the evaporation loss of Mn during smelting and directional solidification, an additional 2 wt.% of electrolytic manganese flakes is added during alloy preparation.

[0082] Step 3, Degassing: Since there may be a small amount of oxides and oxygen in the crucible of the electric arc furnace, titanium is melted for 2-3 minutes before melting the alloy to remove oxides and residual oxygen in the chamber.

[0083] Step 4: Arc Furnace Melting: Place the prepared alloy components in a vacuum arc melting furnace. Place half of the Ni granules at the bottom of the water-cooled copper crucible, then add electrolytic Mn sheets, followed by Ga blocks, and finally top with the remaining half of the Ni granules to reduce losses caused by component volatilization or sputtering during melting. Evacuate the furnace to 10°C. -3 The gas is on the order of Pa, and high-purity argon is introduced. The alloy is then melted. To minimize the volatilization of Mn, the current is controlled to not exceed 250A during melting. Arc stirring is used to homogenize the alloy. The melting is repeated 4 times to finally obtain the alloy button ingot.

[0084] Step 5, wire cutting: The button ingots obtained in Step 4 are cut into round bars with a diameter of 7mm by wire cutting to prepare for subsequent directional solidification and melting.

[0085] Step Six, Directional Solidification: Using the Bridgman method, the round bar obtained in Step Five is placed inside a high-purity corundum ceramic tube with a diameter of 7 mm and a length of 15 mm for heating. The alloy is melted by electromagnetic induction heating with a heating power of 20 KW and held at that temperature for 1 hour to ensure complete melting. Then, the alloy is directionally solidified by pulling at a speed of 10 μm / s. Finally, the sample is quickly placed into Ga-In liquid for cooling.

[0086] The microstructure of the alloy was observed using scanning electron microscopy (SEM), such as... Figure 1 As shown, the alloy after directional solidification is in a oligocrystalline state, with coarse columnar martensite. The martensite grain width reaches 60–100 μm. The grain growth direction is almost parallel to the directional solidification direction, and there are very few transverse grain boundaries perpendicular to the stress direction, which reduces crack initiation and is beneficial to improving the compressive strength and fatigue life of the material.

[0087] The crystal structure of the alloy was determined by X-ray diffraction (XRD), such as... Figure 2 As shown, the alloy is confirmed to consist of two phases: martensite and γ-phase. Differential scanning calorimetry (DSC) revealed the martensitic transformation initiation temperature to be 437.8℃ and the austenitic transformation initiation temperature to be 508.3℃, both above 400℃. Universal testing showed the alloy exhibited a shape memory effect of 3.52%, a fracture strength of 1725 MPa, and a fracture strain of 17%. Electron backscatter diffraction (EBSD) measurements of the crystal orientation and texture revealed the presence of martensitic texture in the

[001] direction, as shown... Figure 5 As shown.

[0088] Because Ni-Mn-Ga alloys are intermetallic compounds, and the atomic sizes and electronic structures of Ni, Mn, and Ga atoms differ significantly, while the atoms are bonded together by metallic bonds, intergranular fracture is prone to occur, leading to brittle fracture of the alloy. In polycrystalline alloys, repeated deformation and shape recovery processes can easily cause cracks to initiate at grain boundaries, resulting in stress concentration and reducing the fatigue life of the material.

[0089] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high-strength and high-temperature nickel-manganese-gallium shape memory alloy, wherein the nickel-manganese-gallium shape memory alloy is prepared from Ni in a molar ratio of 56%~58%, Mn in a molar ratio of 24%~26%, and Ga in a molar ratio of 17%~19%, characterized in that: It includes the following steps: Step 1: Pre-treatment of alloying elements: Step 2, Weighing: Weigh the Ni particles with a diameter of 3 mm and a length of 3 mm, the electrolytic Mn flakes and the Ga block. To compensate for the evaporation loss of Mn during smelting and directional solidification, add 2 wt.% electrolytic manganese flakes during the alloy preparation process. Step 3: Degassing: Before melting the alloy, 100-120g of sponge titanium is melted in a water-cooled copper crucible for 2-3 minutes to remove oxides and residual oxygen in the electric arc furnace. Step 4: Electric Arc Furnace Melting Step 41: Place the prepared alloy components into a vacuum arc melting furnace, and evacuate the furnace to 10°C. -3 The gas is on the order of Pa and filled with high-purity argon. Step 42: Start melting the alloy. To minimize the volatilization of Mn, control the current to no more than 250A during melting. Use electric arc stirring to homogenize the alloy. Repeat melting 4-5 times to finally obtain the alloy button ingot. Step 5, Wire EDM: The button ingots obtained in step four were cut into round bars with a diameter of 7mm by wire cutting to prepare for subsequent directional solidification melting. Step Six: Directional Setting: The round bar obtained in step five was placed inside a high-purity corundum ceramic tube with a diameter of 7 mm and a length of 15 mm using the Brijeman method, and the alloy was melted by electromagnetic induction heating. Finally, the sample was quickly placed into Ga-In liquid for cooling. Thus, the preparation of a high-strength and high-temperature nickel-manganese-gallium shape memory alloy was completed.

2. The method for preparing a high-strength and high-temperature nickel-manganese-gallium shape memory alloy according to claim 1, characterized in that: Step one involves pre-treating each alloying element, including the following steps: Step 11: Select Ni particles with a purity >99.99%, electrolytic Mn flakes with a purity >99.8%, and Ga blocks with a purity >99.9% as raw materials; Steps 1 and 2: Before smelting, soak the Ni particles and electrolytic Mn sheets in anhydrous ethanol solution for 15 minutes, rinse and then blow dry; Step 13: Place the Ga block in a beaker, and then place the Ga block in hot water at 90°C to wait for it to melt.

3. The method for preparing a high-strength and high-temperature nickel-manganese-gallium shape memory alloy according to claim 2, characterized in that: The weighing methods for Ni particles, electrolytic Mn sheets, and Ga blocks in step two are as follows: Step 21: Calculate the mass ratio based on the atomic ratio and the atomic mass of the elements, and weigh the Ni particles, electrolytic Mn sheets and Ga blocks using an electronic balance with an accuracy of 0.0001 g. Step 22: Use a disposable dropper to draw the molten Ga from the beaker and weigh it to obtain the required weight.

4. The method for preparing a high-strength and high-temperature nickel-manganese-gallium shape memory alloy according to claim 3, characterized in that: The alloying element composition weighed in step two is Ni. 57 Mn 25 Ga 18 .

5. The method for preparing a high-strength and high-temperature nickel-manganese-gallium shape memory alloy according to claim 4, characterized in that: The method for placing the prepared alloy components into the vacuum arc melting furnace in step four is as follows: Place half of the Ni particles at the bottom of the water-cooled copper crucible, then add electrolytic Mn sheets, then Ga blocks, and finally add the remaining half of the Ni particles on top.

6. The method for preparing a high-strength and high-temperature nickel-manganese-gallium shape memory alloy according to claim 5, characterized in that: In step 42, the current is controlled at 250A during melting, and electric arc stirring is used to homogenize the alloy. The melting is repeated 4 times.

7. The method for preparing a high-strength and high-temperature nickel-manganese-gallium shape memory alloy according to claim 6, characterized in that: In step six, during the melting process of the alloy using electromagnetic induction heating, the power is increased by 2 KW every 5 minutes until it reaches 20 KW, and then the temperature is maintained for 1 hour. After holding at this temperature, directional solidification is carried out.

8. The method for preparing a high-strength and high-temperature nickel-manganese-gallium shape memory alloy according to claim 7, characterized in that: In step six, the alloy is directionally solidified using a pulling speed of 10 μm / s.

Citation Information

Patent Citations

  • Toughened high-temperature shape-memory alloy and preparation method thereof

    CN101709411A

  • Method for improving strength and plasticity of Ni-Mn-Ga alloy

    CN116837236A